Robust integral of sign of error‐based distributed flocking control of double‐integrator multi‐agent systems with a varying virtual leader - Wang, Ximing; Sun, Jinsheng; Wu, Zixing; Li, Zhitao (International journal of robust and nonlinear control, 2022)
This article investigates the flocking control problem of double‐integrator multi‐agent systems with a virtual leader subject to unknown external disturbances. A robust integral of sign of error (RISE) based control method is leveraged to design a distributed flocking controller with advantages of zero initial input value and continuous control input. By means of a new second‐order differential virtual potential field function, and the navigational feedback from a virtual leader, the proposed flocking controller assures agents of velocity consensus with the virtual leader and a quasi α‐lattice formation within a circular neighborhood centered on the virtual leader. Moreover, this algorithm guarantees collision avoidance and connectivity preservation of a proximity‐induced communication topology. Numerical simulations of the algorithm are provided to illustrate the effectiveness of the proposed flocking algorithm.